Avaliação do desempenho de biomateriais para a construção de um molde vaginal usado em cirurgias de vaginoplastia - Mendes, Luanne Cardoso (2019)
Patients with Mayer-Rokitansky-Küster-Hauser syndrome (MRKH), as well as transsexuals individuals who wish to undergo sex reassignment surgery (CRS) from male to female, are extremely affected by the absence of a vaginal canal. Because of this, these people search for vaginoplasty, the procedure responsible for creating a vaginal cavity. After surgery, a mold (consisting of a base and a covering material) is required to be inserted into the neocavity in order to keep the newly constructed physical structure intact and facilitate channel epithelization. Studies evidenced the lack of vaginal molds in the market, besides the application of improvised alternatives for this conjuncture. In addition, in a recent review of the literature (MENDES, 2017), two materials with favorable characteristics were identified: Cica-Care, representing the base of the mold; and Interceed, as coating material. However, they have not yet been tested and applied together. Thus, the objective of this project was to compare the performance of the two materials with a third one, a sponge, whose function is to induce inflammatory processes in order to observe the level of adhesions formed and the existence or not of inflammation’s cells. An experimental study using 34 rats (Rattus novergicus) Wistar was performed, consisting of four groups: Sponge, Cica-Care, Interceed + Sponge and Interceed + Cica-Care. The molds were created with the materials following the definition of the groups and were implanted in the dorsal region of the animals. After 21 days, the biopsies were performed, the structural adhesion scores were classified, and the materials collected were analyzed histologically and statistically for the following factors: mononuclear infiltrate, polymorphonucleated infiltrate, fibrosis, foreign body reaction and vascularization. For the adhesion scores, significant differences were found between the Sponge x Interceed + Cica-Care groups (p=0.0018), Cica-Care x Interceed + Cica-Care (p=0.0035) and Interceed + Sponge x Interceed + Cica-Care (p<0.0001). For the foreign body reaction factor, a significant difference was found in almost all groups in the two-to-two comparison, except for Cica-Care x Interceed + Cica-Care (p=1). For the other factors, statistical differences were found comparing all groups two to two (p<0.0001). Finally, it can be concluded that Interceed as a coating material allied to Cica-Care as a base are excellent materials that, together, do not induce adhesion formation nor inflammatory processes, representing an excellent alternative for vaginal molds used in surgeries of vaginoplasty.